Evaluación agronómica del sistema cacao (Theobroma cacao L) - banano (Musa Paradisiaca) rehabilitado mediante injerto con tres tipos de fertilizantes foliares - Arias Arias, Lesly Daniela (2025)
Cocoa, Theobroma cacao L, is a tropical climate plant that can be grown from seeds or through vegetative parts, being of great importance for the agricultural sector of the Country due to its genotypes of fine or aroma cocoa, being one of the most valued in the international market for particular characteristics of aroma and flavor. In the research carried out, the Cocoa - Banana system was evaluated agronomically, rehabilitated by grafting with three types of foliar fertilizers. The objectives set were: I) Compare the agronomic characteristics in each of the treatments, II) Determine in which of the treatments we obtain the greatest number of flowers and ears. In this research, descriptive and inferential statistics were applied. Four treatments were used: Actimec, Amingold, Calciliq-A and a control group without foliar fertilization. The evaluation was carried out in two stages, before and 120 days after the application of the fertilizers. The type of analysis, 5% and 1 % Fisher test, 5% Tukey test and correlation and linear regression analysis. Various characteristics were evaluated, such as plant height, number of main branches, number of secondary branches, stem diameter, diameter of secondary branches, fruit length, fruit diameter, number of flower buds, among others. The statistical results show that when applying the T3 treatment with Calciliq-A, it stands out as the most efficient to lengthen the tissues, with an increase of 3.86% in relation to its initial measurement in the height of the plants, it also shows an improvement considerable in the diameter of the crown, diameter of main branches in an increase of 3.33%, stem diameter with an increase of 6.22%, diameter of the ear and a greater length of the fruit, in the productive characteristics an increase in the number was evident. of fruits, flower buds, open and semi-open flowers. This is because the fertilizer is designed to promote flowering, fruit setting and filling. The variability in agronomic responses highlights the importance of carefully selecting the type of foliar fertilizer, considering the specific characteristics of the crop and environmental conditions. The Control treatment provided valuable insights when comparing its performance with the fertilized treatments, highlighting the relevance of fertilization in crop management. It was determined that within the components that constituted the number of cocoa fruits, there were significant correlations in the variable number of flower buds.